Increasing Cattle Herd Size or Density in C3 Grass–Legume Meadows Reduces Dietary Quality - John Derek Scasta; Fernando Forster Furquim (Animals)
Animal density is a grazing management decision implemented by managers that may reduce animal diet quality. Over three years, we collected herd-level cattle samples with varying animal numbers and densities across C3 grass–legume meadows near Powell, WY, USA. Paddocks ranged in size from 3 to 72 ha, cattle groups ranged from 80 to 370 animals, animal units (AUs; defined as heifers = 0.8, cow–calf pairs = 1.3, and bulls = 1.6) ranged from 52 to 248.6, animal density ranged from 1.5 to 30.3 animals/ha, and AU density ranged from 0.9 to 19.8 AUs/ha. Near-infrared reflectance spectroscopy of fecal samples (f.NIRS) was used to estimate crude protein (CP), digestible organic matter (DOM), and the DOM:CP ratio. Structural equation modeling (SEM) that mediated time (i.e., Day of Year) rendered all animal number or density variables as significant predictors for CP and DOM (negative estimates) and for DOM:CP (positive estimate), indicating that congregating animals in larger groups and/or greater densities, even in meadows with high-quality forage species, may reduce post-ingestive diet quality estimates by −1.2% and −2.0 for CP and DOM for every +100 animals or for every +10 animals per hectare. Livestock managers could potentially override this negative effect by adjusting when animals are congregated at higher densities.